PENILAIAN HASIL BELAJAR ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH PENYELENGGARA INKLUSIF SD N 01 LIMAU MANIS (PENELITIAN STUDI KASUS) - Orin Oktorima (Universitas Negeri Padang, 2015)
ABSTRACK Orin Oktorima. 2015. Learning Assessment for the Students with Spesial Needs at Inclusive School SDN 01 Limau Manis ( a Case Study in Class I, II, and IV of SD Negeri 01 Limau Manis Kecamatan Pauh, Sumatera Barat. Thesis. Special Education Department of the Education of State University of Padang. This research was derived from the problems founds on learning assessment for the students with special needs in class I, II, and IV of SD N 01 Limau manis. In completing the tasks assigned, the students’ average score was always below the Minimum Standard Score. Meanwhile their final scores in the learning report did not indicate that they had learning problems as their average score was above the Minimum Standard Score. Therefore, this research was intended to reveal the learning assessment for the students with special needs in inclusive school. This research applied case study approach emphasizing on the criteria of learning assessment for the students with special need, the process of learning assessment for the students with special needs in inclusive school, the problems found in conducting learning assessment for the students with special needs, and the efforts done to overcome the problems found in conducting learning assessment for the students with special needs. The subject of the research was the teachers teaching in class I, II and IV of SD N 01 Limau Manis. The data were collected through observation and interview. The results of the research indicated that in conducting learning assessment, the teachers had lack of understanding on learning assessment for the students with special needs, and there were several aspects that had not been run as they should be. Therefore, it was suggested to the teachers to enhance their knowledge about learning assessment for the students with special needs. Key Terms: Learning Assessment, Students With Special Needs, Inclusive Education